2021
DOI: 10.3390/jcm10143009
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Binding Protein 3 (FABP3) and Apolipoprotein E4 (ApoE4) as Lipid Metabolism-Related Biomarkers of Alzheimer’s Disease

Abstract: Background: Lipid metabolism-related biomarkers gain increasing researchers interest in the field of neurodegenerative disorders. Mounting evidence have indicated the role of fatty acid-binding proteins and pathology lipid metabolism in Alzheimer’s Disease (AD). The imbalance of fatty acids (FA) and lipids may negatively affect brain functions related to neurodegenerative disorders. The ApoE4 and FABP3 proteins may reflect processes leading to neurodegeneration. This study aimed to evaluate the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 69 publications
(167 reference statements)
1
11
0
Order By: Relevance
“…FABP1 is a liver-specific fatty acid-binding protein that plays important roles in intracellular lipid metabolism in the liver, and the knockdown of FABP1 in liver decreased the liver weight and hepatic TG (51). FABP3 seems to be lipid metabolism-related biomarker in Alzheimer's disease (52). Markedly, increase in FABP3 mRNA expression in rats' livers and adipose tissue was reported with high-cholesterol diet (53).…”
Section: Discussionmentioning
confidence: 99%
“…FABP1 is a liver-specific fatty acid-binding protein that plays important roles in intracellular lipid metabolism in the liver, and the knockdown of FABP1 in liver decreased the liver weight and hepatic TG (51). FABP3 seems to be lipid metabolism-related biomarker in Alzheimer's disease (52). Markedly, increase in FABP3 mRNA expression in rats' livers and adipose tissue was reported with high-cholesterol diet (53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in PD, FABP3 is also considered a marker of AD because of its relation with Aβ accumulation [ 86 ]. It was even proposed that FABP3 negatively correlates with the severity of the disease: a large amount of FABP3 was detected in the CSF of AD brains, suggesting its correlation with neurodegenerative processes [ 87 ]. In this regard, considering that FABP3 is primarily found in gray matter, its location in the CSF is uncommon and reflects destructive processes that occur in neuronal membrane lipids [ 88 ].…”
Section: Fatty Acid Binding Proteins In Neurodegenerationmentioning
confidence: 99%
“…Previous studies found that CSF levels of HFABP in AD patients were higher than in MCI subjects and older people without cognition impairment (Chiasserini et al, 2017;Höglund et al, 2017;Dulewicz et al, 2021). Furthermore, other studies found significantly elevated CSF HFABP levels have been described in MCI subjects compared with the cognitively healthy group, but no difference between the dementia group and the progressive MCI subgroup (Guo et al, 2013).…”
Section: Discussionmentioning
confidence: 91%